2015
DOI: 10.1109/twc.2014.2371817
|View full text |Cite
|
Sign up to set email alerts
|

Receiver Design of Radio-Controlled Clocks Based on the New WWVB Broadcast Format

Abstract: The architecture and algorithms for the first alldigital radio-controlled clock receiver for the new WWVB broadcast format are proposed. To address the potentially low signal-to-noise ratio conditions and the relatively large frequency offsets experienced in the receiver, two alternative timing synchronization approaches are investigated, i.e., one based on a maximum-likelihood (ML) criterion and the other based on correlation. We show that the correlation-based synchronization technique reduces the implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It is concluded that hypothesis testing has a clear performance advantage over point estimation only if the sync word is relatively short with respect to frame length (less than 20%). Future work will take into account the large and time-varying frequency offset at the receiver, such as that experienced in RCC receivers [16], [19]. Potential interference should also be considered in designing the synchronization framework.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is concluded that hypothesis testing has a clear performance advantage over point estimation only if the sync word is relatively short with respect to frame length (less than 20%). Future work will take into account the large and time-varying frequency offset at the receiver, such as that experienced in RCC receivers [16], [19]. Potential interference should also be considered in designing the synchronization framework.…”
Section: Discussionmentioning
confidence: 99%
“…Substituting (22) into (19), changing the variable from ν 1−η and − ν 1+η to ν, and using the identity [24] ∞ 0…”
Section: Roc Of Dht In Awgn Channelsmentioning
confidence: 99%
See 2 more Smart Citations